IJCM_297A: Perception and practices of human papilloma virus and it's vaccine among medical students. - Shalini Baby S; Govindu S.; Lakshmi Y. Venkata; Afreen Saleha (Wolters Kluwer Medknow Publications, 2024)
Background: Human Papilloma Virus is a DNA virus that causes wart, precancerous lesions, depending on the site affected increase the risk of cancer of the cervix, vagina, penis, anus, mouth, tonsils or throat. In India, cervical Cancer is the 2nd leading cause of cancer deaths in women aged 15 to 44 yrs. Recombinant vaccines Gardasil and Cervarix have been approved, Due to lack of knowledge, fear of side-effects & high-cost acceptance was found to be poor. Objective: To determine the Perception and practices of HPV virus and its vaccine among medical students. Methodology: A cross-sectional study was conducted from JUNE to AUGUST 2023, in a tertiary care centre, among medical students from 1st to final yr. List of all the students were obtained and 75 participants from each year were selected through simple random sampling using random number table method & total 300 participants were included in the study. Data was collected by using google form, using a self-made validated questionnaire. Data was entered into Microsoft Excel & analyzed using SPSS version 26. Results: The study found that 61.5% of respondents were aware of HPV, with 76.5% believing it causes over 50% of cervical cancer cases. Awareness about mode of transmission was found as 88% sexually, 70.5% through needle sharing & 66.4% during pregnancy. Awareness about preventive measures found that 91.3% knew about condoms as partial protection & 39.7% said OCPs. 80% of participants being aware of the HPV vaccine, only 18.3% received it. reasons for not getting vaccinated were 56.4% had lack of knowledge &16.8% fear of side-effects. 81.9% of them aware of HPV vaccine, 24.4% said HPV vaccine's availability for 9-14 yrs, 36.9% knew about recommended doses, 34.6% about the vaccine type. Conclusion: Despite of having awareness about HPV vaccine only few participants had taken the vaccine.